Are Malaysians Ready to Resume the New Norm? Findings From a Nationwide Study - Suet, Sherilyn Pak Cheng; Farrukh, Muhammad Junaid; Qi, Hee Mei; Saleem, Zikria; Salman, Muhammad; ur Rahman, Aziz; Goh, Khang Wen; Ming, Long Chiau (Frontiers in Public Health, 2022)
Objective The study aimed to evaluate the knowledge, attitude, and practices toward the prevention of coronavirus disease 2019 (COVID-19) among the public in Malaysia. Methods A cross-sectional study was conducted online among the general public in Malaysia from June 2020 to August 2020 between the second and third wave (Phase 3 of the Recovery Movement Control Order). Participants were conveniently recruited through multiple social media platforms to encourage nationwide participation. A patient-administered questionnaire was used to assess their knowledge, attitude, and practice toward the prevention of COVID-19. For descriptive analysis, percentage, mean, and standard deviation (SD) were used to report demographic characteristics and knowledge, attitude, and practice scores. For inferential analysis, t-test, ANOVA, Pearson's correlation, Spearman's correlation, Chi-square test, and Binary Logistic Regression was used to analyze the study variables' differentiation, association, and correlations. The confidence interval selected for this study was 95%. Results A total of 420 respondents participated in this survey. The majority of the participants (n = 412, 98%) were aware of COVID-19. Most participants (60%) learned about the pandemic through social media. About half of the participants had poor knowledge (45.5%) and a negative attitude (43.3%). Participants residing in urban areas showed good preventive practices as compared to those residing in rural areas (P < 0.05). There was a significant association between participants' attitudes and preventive practices toward COVID-19, where the majority of the participants (57.4%) who showed negative attitudes were more likely to follow poor preventive practices. Conclusion Despite having good knowledge, participants with a negative attitude toward COVID-19 were less likely to follow the preventive practices of COVID-19. People's mindset and willingness may play an important role to influence their practices. Thus, these are the vulnerable groups, and strategies should be made to change their mindset through proper counseling and education.